Beyond DNA repair: the novel immunological potential of PARP inhibitors - Chabanon, Roman M. (Mol Cell Oncol, 2019)
Loss of excision repair cross-complementation group 1 (ERCC1), frequently found in lung cancer, and mutations in breast cancer type 1/2 susceptibility genes (BRCA1/2), often found in ovarian, breast and prostate cancers, confer sensitivity to poly-(ADP-ribose) polymerase inhibitors (PARPi). Our work, and that of others, shows that PARPi selectively trigger tumor cell-autonomous immune phenotypes in ERCC1- or BRCA-defective contexts. This suggests that PARPi, used in appropriately selected populations, might mediate their therapeutic effects by potentiating anti-tumor immunity.